Breaking the silence on special needs children in foster care: The diversity of children in foster care, carers and processes. (4th October 2021) - Fuentes‐Peláez, Nuria; Montserrat, Carme; Sitjes‐Figueras, Rosa; Crous, Gemma
Abstract: This study aims to advance the understanding of children with special needs in foster care by identifying the characteristics, processes, and outcomes of their placement. The study uses a quantitative approach to identify 190 children with special needs (registered) from among 2, 157 foster children in Catalonia and the Balearic Islands, Spain and examines key data covering 2008 to 2018. The results show that children with special needs are overrepresented in placements with single‐parent foster carers (mainly women), raising questions about the extent to which the care system takes the complexity of special needs into account.